USING COMPUTER TECHNOLOGY IN INTERSUBJECT PROJECTS OF PHYSICS DURING THE STUDY PRACTICE. - N. Guy (Kherson State University, 2010)
This article discusses the use of computer technology in the performance of students in physics interdisciplinary projects during the academic practice.